The Effect Of Work Environment On Employee Performance Through Motivation And Job Satisfaction As Intervening Variables On Permanent Employees - Dinar Agus Sara; Agung Wahyu Handaru; Osly Usman (Green Publisher Indonesia, 2022)
The issue is that employees' expectations of the organization in terms of rewards in the form of pay, benefits, and development to keep up with the flow of progress are still insufficient, and employees have a longer extension time. The purpose of this study is to investigate the impact of the work environment on employee performance using motivation and job satisfaction as intervening variables. The Partial Least Square (PLS) method will be used to analyze the data used to test this research. Previous research which has similarities with this study in terms of the number of variables and the presence of intervening variables is one of the basic references. Researchers chose to use the PLS method that the work environment has significant effect on motivation and the hypothesis is accepted, the work environment has a significant effect on job satisfaction and the hypothesis is accepted, motivation has a significant effect on employee performance and the hypothesis is rejected, job satisfaction has not significant effect on employee performance and the hypothesis is rejected, and the work environment has a significant effect on employee performance and the acceptance hypothesis, and through research indirectly results that the work environment has not significant effect on employee performance through motivation and the hypothesis is rejected, and the work environment has not significant effect on employee performance through employee satisfaction and the hypothesis is rejected, is expected to have a dominant influence so that every employee has the awareness to cultivate a good attitude in the work environment. According to the research, substantial motivation is required, such as providing staff promotions, to boost employee happiness and performance in the organization.